The impacts of altering biodiversity to the Water–Energy–Food nexus: case study North Euboea, Greece - G.-Fivos Sargentis; Romanos Ioannidis (Discover Water)
Abstract The Water–Energy–Food (WEF) nexus is defined in modern societies through a complex interaction of trade, transportation of goods, energy generation technologies and many other parameters. However the dynamics of the WEF nexus are often ignored by technical and scientific communities. The systemic nature of the WEF nexus emphasizes the various interconnections between water, energy, and food, promoting the adoption of a holistic approach, in which the interlinkages highlight synergies and trade-offs and lead to more successful resource management. In contemporary times resources seem abundant as shortages are easily covered by trade and therefore land is often used without evaluating where it could be more productive and potential dangers to the stability of the WEF can be neglected. In this work, the dynamics of the WEF nexus are investigated, evaluating the efficiency of land in relation to the elements of the nexus. As a case study, we chose North Euboea, Greece, specifically focusing on the Municipality of Mantoudi-Limni-Agia Anna. Although the WEF nexus has been increasingly studied, few works have particularly focused on how ecosystem changes disrupt the interlinkages between the nexus components. This study addresses this gap by focusing on the effects of biodiversity alterations (specifically wild boars) on the WEF nexus in a rural Mediterranean context. We explored land use patterns, energy needs, and water requirements for inhabitants, agriculture and livestock for food production, under several assumptions. It is found that if land was used solely for energy production, the energy generated would suffice for the energy consumption of 200,000 inhabitants. The potential of land use for food production on the other hand is corresponding to the food needs of 200,000–300,000 inhabitants. Lastly, as an investigation of the sensitivity of the WEF nexus to environmental stresses, we create a model for the potential impact from the expansion of the local wild-boar population that has been identified as an emerging stress for the local agricultural sector, with potential of diminishing local agricultural production within a few years.